Designing High Performance Factory Automation Applications on Top of DDS. (22nd April 2013) - Calvo, Isidro; Pérez, Federico; Etxeberria-Agiriano, Ismael; de Albéniz, Oier García
DDS is a recent specification aimed at providing high-performance publisher/subscriber middleware solutions. Despite being a very powerful flexible technology, it may prove complex to use, especially for the inexperienced. This work provides some guidelines for connecting software components that represent a new generation of automation devices (such as PLCs, IPCs and robots) using Data Distribution Service (DDS) as a virtual software bus. More specifically, it presents the design of a DDS-based component, the so-called Automation Component, and discusses how to map different traffic patterns using DDS entities exploiting the wealth of QoS management mechanisms provided by the DDS specification. A case study demonstrates the creation of factory automation applications out of software components that encapsulate independent stations.